Analisis Kemampuan Literasi Sains Pada Materi Mengubah Bentuk Energi Di Kelas IV Sekolah Dasar - Nur Alfiah; Muflikhul Khaq; Nur Ngazizah (Departement of Mathematics Education, 2024)
This research aims to determine scientific literacy skills in the material of changing forms of energy in class IV elementary school. This type of research is descriptive qualitative research. The data collection techniques used are observation, interviews, tests and documentation. The results of the research show that the fourth grade science literacy abilities of SD N Keseneng are at the advanced, proficient and basic competency levels. Students with scientific literacy skills at an advanced competency level are able to understand indicators in the aspects of content, process, context, and show a positive attitude. Students with scientific literacy skills at a proficient competency level are able to understand indicators in the content aspect and show a positive attitude. It's just that the responses from students on the process aspect or on the context aspect have not met the indicators. Students with scientific literacy skills at the basic competency level are not yet able to understand the indicators in the content and context aspects of the material on changing forms of energy.